Characterization of a Subset of Patients With Rheumatoid Arthritis for Whom Current Management Strategies are Inadequate. Issue 3 (22nd April 2019) - Bradford, Claire M.; McDonnell, Thomas; Raj, Divya; Robinson, George A.; Cole, Andrew; Ramakrishnan, Shashank; González‐Serrano, Rosa; Mak, Jasper; Eskiocak, Yusuf Cem; Isenberg, David A.; Ciurtin, Coziana; Jury, Elizabeth C.; et al.
Abstract: Objective: A subset of patients with seropositive rheumatoid arthritis (RA) do not mount a C‐reactive protein (CRP) response during flares. We hypothesize that these patients are more likely to experience poor clinical care and less likely to respond to traditional therapy. This study questioned whether this presentation was associated with worse disease outcome and distinct immunological features. Methods: Using Power Doppler ultrasound, 48 RA patients with active synovitis were recruited; 30 had normal (n)CRP (5 mg/L or less) and 18 had high (h)CRP (more than 5 mg/L) levels. All had equivalent disease burden assessed by other clinical and laboratory parameters. Results: Time to diagnosis and time to first disease‐modifying antirheumatic drug were significantly longer in nCRP compared with hCRP patients ( P < 0.05). Significantly more nCRP patients needed escalation to biologics after 2‐year follow‐up ( P = 0.01). The inflammatory milieu was also different between the two subgroups. Synergy between inflammatory cytokines observed in hCRP patients was lost in nCRP patients, and nCRP patients had significantly increased regulatory T‐cell (Treg) frequencies that correlated positively with predictors of poor disease outcome. Conversely, hCRP but not nCRP patients demonstrated a significant upregulation of alternative complement pathway factors that correlated negatively with Treg frequency. Conclusion: Patients with nCRP during flares of RA had an altered immunological profile compared with hCRP patients and experienced diagnostic delays and responded less favorably to conventional treatment.